APLIKASI SISTEM PAKAR DIAGNOSA PENYAKIT GIGI METODE FORWARD CHAINING DI UPTD KESEHATAN PUSKESMAS BANGIL - Kurniawan Wahyu Haryanto; Ari Dwi Cahyono (Joutica, 2019)
Teeth are organs that are very important and very vital. Therefore dental health is very important. Most of the Indonesian people, the appeal for dental examinations every six months is more often considered a breeze then, because they are more concerned with the health of other organs. Though diseases that attack teeth can have a very significant effect such as appearance problems. This research applies computer science in the medical field, especially for dental disease problems at the UPTD Health Center in Bangil using the expert system concept. Expert system is a system in the form of computer software where the computer is made as if - will think like an expert or expert in the field. The search method used is forward chaining, which is a search where facts are known to support conclusions. This expert system makes it easy for patients to conduct consultations, making it easier for the admin to manage symptom data and their illnesses and patient data, judging from the results of the questionnaire which states that it is very useful, can be used as a temporary doctor.